Transition metals cobaltites spinel for depollution of NOx emissions using SCR technology - Yadav D.; Kavaiya A.R.; Mohan D.; Prasad R. (My University, 2025)
The catalytic performances of various transition metal cobaltites prepared by the nanocasting method were investigated for the selective catalytic reduction (SCR) of NO under lean burn conditions. KIT-6 was used as a hard template in the nanocasting method for preparation of catalysts. The catalyst samples were characterized by various techniques such as XRD, low-temperature N2 physisorption, SEM-EDS, and XPS. The catalysts were examined for the SCR of NO by NH3 and H2-LPG in a packed bed tubular flow reactor under the following reaction conditions: 500 ppm NO, 8% O2, in Ar with 200 mg catalyst. The inlet and outlet gases of the reactor were analyzed by an Eco Physics CLD 62 chemiluminescence NO/NOx analyzer and online GC. NO and NO2 measurements were done by an Eco Physics CLD 62 chemiluminescence NO/NOx analyzer. Two separate GCs equipped with Porapak Q/capillary columns and FID/ECD detectors were used to analyze the hydrocarbons/−N2O respectively. The addition of 1% H2 with LPG promoted NO reduction at a remarkably low temperature. It was found that the nature of the dispersed metal strongly affects the light-off temperature (52 °C) and enhances NO conversion. The oxygen-deficient MnCo2O4 spinel structure enhanced NO reduction at a lower temperature of 250 °C as compared to Cu and Ni cobaltites using H2-LPG-SCR. The H2-LPG reductant showed the best de-NOx activity.